The argumentative connecting construction [p(a)ra lá de X]: an usage-based analysis - Rios de Oliveira, Mariangela (2021)
In this article, we investigate the argumentative connecting construction formed by the subparts para, lá and de, plus an element X, which can be an abstract name or a reduced infinitive sentence, coded as [p(a)ra lá de X]CA. This construction is divided into two subgroups, depending on the completion of X. From the perspective of Usage-Based Linguistics, in terms of Traugott and Trousdale (2013) and Hilpert (2014), among others, we assume that this scheme is configured as a member of class of argumentative connectors of Portuguese, competing with other members of this category for instantiation in contemporary use. In qualitative analysis, we found that [p(a)ra lá de X]CA is a complex construction, partially schematic and compositional, not very productive in the language, fulfilling a grammatical function, instantiated as another strategy of persuasion available to users.